2014
DOI: 10.1155/2014/301713
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Cannabis Use among Individuals with HIV/AIDS in Maritime Canada

Abstract: Prolonged previous cannabis consumption and the substantial overlap between recreational and medicinal cannabis use highlight the challenges in obtaining a tenable definition of medicinal cannabis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…The rates of chronic alcohol consumption and abuse are higher in persons living with HIV/AIDS (PLWHA) than the general public, and rates of heavy alcohol use are reported by 40 to 50% of patients surveyed (Braitstein et al 2001; Chitsaz et al 2013; Furler et al 2004). Similarly, PLWHA have a higher prevalence of cannabis use than that of the general population (Braitstein et al 2001; Chitsaz et al 2013; Furler et al 2004; Harris et al 2014). Alcohol and illicit drug use are significant predictors of non-adherence to ART (Bell et al 1998; Bing et al 2001; Khalsa and Royal 2004; Lee et al 2001; Nair et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of chronic alcohol consumption and abuse are higher in persons living with HIV/AIDS (PLWHA) than the general public, and rates of heavy alcohol use are reported by 40 to 50% of patients surveyed (Braitstein et al 2001; Chitsaz et al 2013; Furler et al 2004). Similarly, PLWHA have a higher prevalence of cannabis use than that of the general population (Braitstein et al 2001; Chitsaz et al 2013; Furler et al 2004; Harris et al 2014). Alcohol and illicit drug use are significant predictors of non-adherence to ART (Bell et al 1998; Bing et al 2001; Khalsa and Royal 2004; Lee et al 2001; Nair et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis users more often smoked and drank alcohol than non-users and had more often tried cannabis in early adolescence, were younger, more often males and had lower income and lower socioeconomic status than non-users (11,12). In individuals with HIV, lower income, tobacco smoking, ecstasy use and living in a rural areas were associated with cannabis use (9), while in a study of multiple sclerosis, tobacco-smoking, greater disability according to patients' self-evaluation (especially in the lower limbs), and marriage or being in a stable relationship were associated with cannabis use (7).…”
mentioning
confidence: 97%
“…The cannabinoid system plays a role in inhibiting synaptic transmission and controlling synaptic plasticity in pain and motor pathways through activation of the G-protein-coupled cannabinoid receptors CB1 and CB2. The 2 best-studied constituents of cannabis are Δ 9 -Tetrahydrocannabinol (THC), which binds preferentially at CB1 receptors and has high psychoactive effects and abuse potential, and cannabidiol (CBD), which has limited psychoactive effects (4). Individuals with SCI have, in several studies, reported that cannabis use relieves their pain and spasticity (5,6), but our knowledge of the extent and characteristics of cannabis use in the SCI population in Denmark is inadequate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis is widely consumed in the United States [1], particularly among people living with human immunodeficiency virus (HIV) [2][3][4], and this has fostered an important debate regarding the impact of cannabis on virologic and inflammatory biomarkers. On one hand, a recent study reported reduced adherence to antiretroviral therapy (ART) and retention in care in cannabis users [5], and 2 other studies found no effects of cannabis on viral suppression [4,6].…”
mentioning
confidence: 99%